PENGARUH KUALITAS LAYANAN, KEBIJAKAN HARGA DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN SERTA DAMPAKNYA PADA KEPUASAN KONSUMEN - Mat Amin; Hamdan Hamdan; Ahmad Yani (LPPM STIE PERTIBA Pangkalpinang, 2018)
This Study aims to analyze the effect of quality of service, price, and promotion to customer satisfaction that impact on customer decision. The sample used is customer satisfaction conducted for 5 (five) years. The Research instrument uses income and consumer response data on price and promotion cost for 5 (five) Years. Data analysis techniques used are data analysis, classical assumption test, the coefficient of determination, multiple linear regression analysis and testing of hypothesis test F and t-test. The results showed that the variable quality of service prices and promotion costs together or partially have a positive and significant impact a customer satisfaction that impact on customer decisions